Syndicate Group Discussion Combination with Brain Gym on Anxiety in Pulmonary Tuberculosis: Quasy Experiment Study - Putri Santoso, Shelfi Dwi Retnani; Sasmito, Nanang Bagus (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2020)
East Java is the province in Indonesia with the 2nd most BTA+ lung TB in 2018. The Programs that have been developed and carried out by the government have no programs that are able to overcome the psychological problems of people with TB. Intervention is needed to address the anxiety problems of pulmonary TB clients so that the treatment and therapy that must be undergone by the sufferer can run effectively. The purpose of this study was to identify the effect of syndicate group discussion combination with brain gym on anxiety in pulmonary TB. In a quasi-experimental study with pre and post-test design, 60 participants (30 in the treatment group and 30 in the control group) were selected by convenience sampling. The instrument used HARS. Data analysis used is the Mann Whitney and Wilcoxon Sign Rank Test. The mean scores about anxiety before and after the intervention of the treatment group (30,63 to 9,97)) and control group (31,03 to 20,73). Wilcoxon test result showed that this intervention significantly decreases anxiety (p=0,001). And Mann Whitney result showed a difference in anxiety between the treatment and control group (p=0,001). This combination can be applied to decrease the anxiety of clients with lung TB. Further research is needed on the same intervention, but the addition of a cortisol hormone assessment in assessing anxiety in clients as one of the variables. Abstrak: Jawa Timur merupakan provinsi di Indonesia dengan posisi ke-2 kejadian BTA+ kasus TB paru di Tahun 2018. Program-program yang dikembangkan dan dilakukan oleh pemerintah belum ada mengenai penatalaksanaan tentang masalah psikologis penderita TB paru. DIperlukan intervensi untuk mengatasi masalah kecemasan klien TB, supaya pengobatan dan terapi yang wajib dijalani klien TB dapat berjalan efektif. Penelitian ini bertujuan untuk mengetahui pengaruh syndicate group discussion kombinasi brain gym terhadap kecemasan pada klien TB paru. Penelitian Quasi experiment dengan rancangan pre dan post design, 60 responden (30 kelompok intervensi dan 30 kelompok kontrol) dipilih dengan teknik convenience sampling. Instrumen menggunakan HARS. Analisa data menggunakan Mann Whitney dan Wilcoxon Sign Rank Test. Nilai rata-rata kecemasan sebelum dan sesudah dilakukan intervensi kelompok perlakuan (30,63 ke 9,97) dan kelompok kontrol (31,03 ke 20,73). Hasil uji Wilcoxon menunjukkan intervensi ini secara signifikan menurunkan kecemasan (p=0,001). Dan Hasil uji Mann Whitney menunjukkan ada perbedaan kecemasan antara kelompok perlakuan dan kontrol. Kombinasi ini dapat diaplikasikan untuk menurunkan kecemasan pada klien dengan TB paru. Penelitian selanjutnya, dengan intervensi yang sama, dapat menambahkan nilai hormone kortisol sebagai salah satu variabel penilaian kecemasan.